2019
DOI: 10.1371/journal.pone.0216332
|View full text |Cite|
|
Sign up to set email alerts
|

Women’s views about contraception requirements for biomedical research participation

Abstract: The scientific and ethical importance of including women of reproductive age in biomedical research is widely acknowledged. Concerns about preventing fetal exposure to research interventions have motivated requirements for contraception among reproductive aged women in biomedical studies–often irrespective of risks and benefits or a woman’s actual potential for pregnancy, raising important questions about when such requirements are appropriate. The perspectives of women themselves on these issues are largely u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 29 publications
0
22
0
Order By: Relevance
“…Especially in resourcelimited settings key issues pertaining to the use of contraceptives in adolescent girls such as cultural norms, religious beliefs, community perspectives and stigma (for HIV and contraceptive use), might pose major enrolment concerns and could be addressed during the trial planning phase [31]. Raising community awareness and education is also crucial [32].…”
Section: Contraception In Adolescencementioning
confidence: 99%
“…Especially in resourcelimited settings key issues pertaining to the use of contraceptives in adolescent girls such as cultural norms, religious beliefs, community perspectives and stigma (for HIV and contraceptive use), might pose major enrolment concerns and could be addressed during the trial planning phase [31]. Raising community awareness and education is also crucial [32].…”
Section: Contraception In Adolescencementioning
confidence: 99%
“…Despite the advice provided in the ICH M3(R2) guidance [ 2 ] and the Clinical Trial Facilitation Group (CTFG) recommendations [ 3 ], unintended pregnancies in biomedical research are still a matter of concern as evidenced in recent publications [ 4 , 5 , 6 , 7 ]. A 2018 paper [ 6 ] reports wide variation in pregnancy testing plans in clinical trials, leading to the potential for inadequate protection against embryonic or fetal exposure in some cases and unnecessary burdens on research participants in others.…”
Section: Discussionmentioning
confidence: 99%
“…An industry survey on birth control in clinical trials revealed that few companies collected data in a manner that would allow retrospective understanding of the reasons for the failure of birth control in clinical trials [ 7 ]. Among other causes, one reason for unintended pregnancies in the setting of clinical trials could be that the perspectives of women themselves on contraception in research are largely unexplored [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…The studies included in our analysis that took place during the same time period as the HVTN 503 trial recorded an average incident pregnancy rate of 4.6/100 w-yr, which was higher than the 2.3/100 w-yr recorded in subsequent trials and may in part be due to increasing availability of contraception options and, at least at some sites, a more structured approach to providing on-site effective contraception during this time. Indeed, HIV prevention researchers have actively sought correlates of incident pregnancy to identify potential participants with higher pregnancy risk prior to study entry and exclude them for reasons of trial efficiency and due to the lack of pre-clinical safety data in pregnancy 10,[20][21][22] . Increasing attention is being given to addressing vaccine safety during pregnancy and the ethics of conducting vaccine research among pregnant women 8,15,16,23 , including the rights and needs of high-risk populations who generally form the study population for efficacy trials of novel HIV prevention products 24 .…”
Section: Discussionmentioning
confidence: 99%